2017
DOI: 10.1167/iovs.17-21546
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Angiotensin-Converting Enzyme 2 Ameliorates Amyloid β-Induced Inflammatory Response in Human Primary Retinal Pigment Epithelium

Abstract: Overexpression of angiotensin-converting enzyme 2 ameliorates amyloid b-induced inflammatory response in human primary retinal pigment epithelium. Invest Ophthalmol Vis Sci. 2017;58:3018-3028. DOI:10.1167/ iovs.17-21546 PURPOSE. Amyloid-b (Ab) is a major constituent of drusen, which is a hallmark of early AMD. The purpose of this study was to investigate whether enhancement of ACE2, an important component of the protective angiotensin-converting enzyme 2 (ACE2)/Ang-(1-7)/Mas axis of the renin angiotensin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Activation of endogenous Ace2 by diminazene aceturate facilitates the drainage of aqueous humor and decreases intraocular pressure in a rat model of glaucoma [34]. Overexpression of ACE2 can also ameliorate the inflammatory response in experimental autoimmune uveitis model and amyloid β-treated human RPE [35,36]. Although ACE2 is critical for SARS-CoV infection, SARS-CoV infection and spike protein of SARS-CoV would reduce ACE2 expression, and injection of SARS-CoV spike protein worsens acute lung failure in mice with the enhanced renin-angiotensin pathway [37].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of endogenous Ace2 by diminazene aceturate facilitates the drainage of aqueous humor and decreases intraocular pressure in a rat model of glaucoma [34]. Overexpression of ACE2 can also ameliorate the inflammatory response in experimental autoimmune uveitis model and amyloid β-treated human RPE [35,36]. Although ACE2 is critical for SARS-CoV infection, SARS-CoV infection and spike protein of SARS-CoV would reduce ACE2 expression, and injection of SARS-CoV spike protein worsens acute lung failure in mice with the enhanced renin-angiotensin pathway [37].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in a good agreement with previous findings demonstrating that ACE2 activity was significantly reduced in the brain of AD patients compared with age-matched controls and correlated inversely with levels of Aβ and phosphorylated tau [ 25 ], ACE2 activity also showed a tendency to decrease in the serum of AD patients compared with normal controls [ 24 ]. ACE2 is considered to influence Aβ metabolism as converting the longer and neurotoxic forms of Aβ (Aβ43) to the shorter, less toxic forms of Aβ [ 24 ] as well as ameliorating Aβ-induced inflammatory response [ 26 ]. Thus, we suggest that the disturbance in Ace2 expression in the brain of OXYS may partially contribute to Aβ metabolism alterations in rats of this strain.…”
Section: Discussionmentioning
confidence: 99%
“…Fu and colleagues in 2017 transfected ACE2 plasmid in primary cultured human retinal pigment epithelium cells (hRPE) followed by stimulation with amyloid-β (Aβ). They observed that overexpression of ACE2 markedly decreased Aβ-induced inflammatory response by activating the ACE2/ Ang-(1-7)/Mas pathway in hRPE [42]. In the respiratory syncytial virus, ACE2 protected against severe lung injury both in children and an experimental mouse model.…”
Section: Aging and Angiotensin-converting Enzyme 2 Receptor (Ace2)mentioning
confidence: 99%